The perception of Istanbul's chromatic identity through urban furniture: A study on college of communication students - (:unkn) unknown (Peter Lang AG, 2021)
Color, as a component of urban identity, illustrates the cultural ties of a city and highlights its distinctive qualities, shaping the image. The colors of city furniture are, therefore, a significant component in terms of the identity of a city. The research, in which we processed the survey results of the college of communication students, Marmara Unversity, has revealed that color is a component of the urban identity; there is a correlation between urban furniture and this urban identity; although participants have certain awareness of the colors of urban furniture, they do not have a common sense of color regarding the city of Istanbul. © Peter Lang GmbH. Internationaler Verlag der Wissenschaften Berlin 2020. All rights reserved.
Keywords: City color; Urban furniture; Urban identity; Urban planning; Visual identity